2019
DOI: 10.32771/inajog.v7i3.1037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Implementation of Obstetric Referral Cases to the Emergency in the JKN Era

Abstract: Abstract Objective: To investigate the circumstances of the obstetric referral case at the emergency department of the Dr.Cipto Mangunkusumo Hospital as well as the accuracy of the referral implementation. Method: We used cross-sectional study. Medical records of obstetric patients at Emergency department in RSCM in January 2013-July 2014 were obtained, then information about patients and their characteristic were collected. The accuracy of referral cases is based on emergency obstetric criteria by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…With a reduced portion of referrals from community health centers or clinics and an increase in the portion of referrals from type-D hospitals, we suspect an increase in tiered referral compliance. 16 On the other hand, an increase in referrals from type-A hospitals to RSCM was found in this study. This is interesting, considering that it is not common for type-A hospitals to make referrals to another type-A hospitals.…”
Section: Discussioncontrasting
confidence: 40%
See 4 more Smart Citations
“…With a reduced portion of referrals from community health centers or clinics and an increase in the portion of referrals from type-D hospitals, we suspect an increase in tiered referral compliance. 16 On the other hand, an increase in referrals from type-A hospitals to RSCM was found in this study. This is interesting, considering that it is not common for type-A hospitals to make referrals to another type-A hospitals.…”
Section: Discussioncontrasting
confidence: 40%
“…17 Most of the patients referred to RSCM were multiparous patients both before and during the pandemic, in contrast to the fi ndings that most of the referral patients were nulliparous patients, which ranged from 38.1 to 52.4%. 16 On the other hand, this study and the research of Madjid et al16 both reported patients of gestational age 29 weeks or more like the most frequently referred to the RSCM. The diagnosis of most obstetric referral cases is the high-risk pregnancy.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations